2006
DOI: 10.1002/pbc.20819
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea therapy lowers TCD velocities in children with sickle cell disease

Abstract: HU-treated patients experienced statistically significant decreases in TCDi velocities compared to age-matched controls. Changes in hematologic parameters were not predictive of changes in TCDi velocities in the treated group. The decrease in TCDi velocities is not a consequence of changes in hematologic values in patients treated with HU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 18 publications
4
45
0
2
Order By: Relevance
“…353 In another study, the adjusted mean change in TCD velocities was -13.0 cm/s (95% CI, -20.19 to -5.92) in an hydroxyurea-treated group and ϩ4.72 cm/s (95% CI, -3.24 to 12.69) in controls (PϽ0.001). 369 Children (nϭ59) for whom hydroxyurea therapy was initiated for clinical severity who had pretreatment baseline TCD measurements, 37 of whom had increased flow velocities (Ն140 cm/s), were enrolled in a prospective phase 2 trial with TCD velocities measured at maximum tolerated dose and 1 year later. 370 At hydroxyurea maximum tolerated dose [mean Ϯ1 standard deviation (SD)ϭ27.9Ϯ2.7 mg/kg per day), decreases were observed in bilateral middle carotid artery velocities.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…353 In another study, the adjusted mean change in TCD velocities was -13.0 cm/s (95% CI, -20.19 to -5.92) in an hydroxyurea-treated group and ϩ4.72 cm/s (95% CI, -3.24 to 12.69) in controls (PϽ0.001). 369 Children (nϭ59) for whom hydroxyurea therapy was initiated for clinical severity who had pretreatment baseline TCD measurements, 37 of whom had increased flow velocities (Ն140 cm/s), were enrolled in a prospective phase 2 trial with TCD velocities measured at maximum tolerated dose and 1 year later. 370 At hydroxyurea maximum tolerated dose [mean Ϯ1 standard deviation (SD)ϭ27.9Ϯ2.7 mg/kg per day), decreases were observed in bilateral middle carotid artery velocities.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…Several case series and retrospective reviews have found a benefit of hydroxyurea in lowering TCD velocities in patients with abnormal TCD velocities, but no history of stroke [163,164]. As mentioned previously, in the BABY HUG study, TCD velocities increased at a slower rate in infants who received hydroxyurea compared with those who received standard care [145].…”
Section: Discontinuation Of Primary Stroke Prevention Strategiesmentioning
confidence: 79%
“…Recognizing this significant barrier, several investigators evaluated hydroxyurea therapy as an alternative to regular transfusions for stroke prevention. Based on several studies that consistently demonstrated a decrease in TCD measurements with hydroxyurea therapy [66][67][68][69][70][71], the NHLBI sponsored the Transcranial Doppler With Transfusions Switching to Hydroxyurea (TWiTCH) trial. For primary stroke prevention, the TWiTCH trial randomly allotted children with hemoglobin SS and hemoglobin S/beta-0-thalassemia with elevated TCD velocities without strokes and were on a regimen of regular transfusions to receive either regular blood transfusion therapy or hydroxyurea therapy escalated to maximum tolerated dose.…”
Section: Stroke Prevention In Scamentioning
confidence: 99%